PENGARUH KUALITAS AUDIT TERHADAP PREDIKSI LABA DAN TINGKAT PENGEMBALIAN INVESTASI DI MASA MENDATANG (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Wulan Oktaviani; Tarmizi Achmad (Diponegoro Journal of Accounting, 2022)
This study aims to examine and analyze the effect of audit quality on earnings predictions and the rate of return on investment. The research variables used in the test are audit quality as an independent variable, and predictions of profit and return on investment as the dependent variable.The population used in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. The research sample was obtained using the purposive sampling method, so that as many as 285 samples were obtained in the study. This research uses multiple regression model in analyzing the data.The test results in this study prove that audit quality has no significant effect on earnings predictions or has a negative effect on earnings predictions. Beside that, on the second dependent variable, namely investment returns, audit quality has a significant effect on investment returns or has a positive effect on investment returns.